Evaluasi Kinerja Ruas Jalan Soekarno-Hatta, Kota Dumai - Muhammad Idham; Wiwi Safitri (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2021)
The creation of a transportation system that ensures the movement of people, vehicles, and or goods smoothly, safely, quickly, cheaply, comfortably, and by the environment is already a development goal in the transportation sector. The target functional level of the road network will be determined by the level of traffic flow through the road network. Based on data from the Central Bureau of Statistics in 2017, Dumai City has national roads with a total length of 72 km, and provincial roads with a total length of 140 km. Every day nearly thousands of vehicles pass through that road. The trip that is carried out can cause quite a lot of displacement at the same time and has the potential to cause high travel generation. This activity certainly can result in jams. As a national road, Jalan Soekarno-Hatta must meet the requirements of comfort and safety so that traffic on this road can run well. Therefore, it is necessary to evaluate the road performance. The purpose of research is to find out the value of the degree of saturation and the value of the level of service on that road. The evaluation on the research by using PKJI 2014. Of the evaluations carried out, it is known that the Soekarno-Hatta road segment will experience congestion on Saturdays and Sundays. The highest peak hour is on Sunday at 14:00-15:00 WIB with a volume of vehicle 2300 vehicles/hour. Soekarno-Hatta's service level on Monday and Tuesday is in class D, while on Saturday and Sunday, the level of road service is in class F. Thus it can be concluded that the performance of the Soekarno-Hatta road section is classified as poor, so that action is needed for the future.